(untitled) (Research, Society and Development, 2021)
The object of study is the perception of the nursing staff in relation to therapeutic play as pain relief and reduction of drugs in the pediatric ward. The guiding question was based on the following question: What is the importance of therapeutic play in nursing care for children admitted to a pediatric ward? The general objective was to demonstrate the importance of differentiated nursing care in the pediatric ward sector using the therapeutic toy. The specific objectives were: to describe the difficulties that children face during hospitalization and to list the techniques that facilitate the children’s adaptation during the hospitalization process. This course completion work consists of a literature review. The literature search was performed in the following databases: Medical Literature Analysis and Retrieval System Online (MEDLINE); Nursing Database (BDENF); and Latin American and Caribbean Literature on Health Sciences (LILACS), through the Virtual Health Library (VHL). It is concluded, in this research, that the therapeutic toy is an essential tool in nursing care in the pediatric ward. In this context, regarding the lactating phase, the use of exercise games was the most suitable for this age group.